ความสัมพันธ์ของอินทรียวัตถุกับค่าความเป็นกรดของพืชหมักบางชนิด - ปัญญาทอง, มนตรี; บูรณวิทย์, กฤตภาค (Health Science, Science and Technology Reviews, 2014)
ผลการศึกษาความสัมพันธ์ของอินทรียวัตถุกับค่าความเป็นกรดของพืชหมักบางชนิดพบว่าปริมาณอินทรียวัตถุของพืชหมัก 3 ชนิดคือ เปลือกและซังข้าวโพด ผักตบชวา และหญ้าขน มีแนวโน้มลดลงตามค่า pH ที่ลดลงในสัปดาห์ที่ 2 ของการหมัก และคงที่ตลอดระยะเวลาการหมัก 8 สัปดาห์ โดยพบว่า เปลือกและซังข้าวโพดหมักมีค่าอินทรียวัตถุเฉลี่ยสูงที่สุด (79.19 ± 1.53 %) ตามด้วยหญ้าขนหมัก (75.57 ± 0.59 %) และผักตบชวาหมัก (63.68 ± 3.75 %) ตามลำดับ (p<0.05) ส่วน pH เฉลี่ยของผักตบชวาหมักมีค่าต่ำสุด (3.93 ± 0.79) รองลงมาคือเปลือกและซังข้าวโพดหมัก (4.71 ± 0.35) และหญ้าขนหมัก (4.73 ± 0.18) ตามลำดับ (p<0.05) ผลการศึกษาแสดงให้เห็นถึงความสัมพันธ์ที่เป็นไปในทิศทางเดียวกันคือปริมาณอินทรียวัตถุในพืชหมักจะลดลงเมื่อค่า pH ของการหมักลดต่ำลง The relationship of organic matter to the pH of some silages Montri Punyatong1* and Krittaphak Buranawit1 1Major of Animal Science, School of Agriculture and Natural Resources, University of Phayao, Phayao Province 56000 Silage is the roughage sources for ruminants in times of scarcity. The study was found that the amount of organic matter in 3 types of silage plants as husk and corn cobs, water hyacinth and Para grass tends to decrease with the pH level which decreased in week 2 of fermentation and constant throughout the 8 week of fermentation period. The average organic matter of husk and corn cob silage was highest (79.19 ± 1.53), followed by Para grass silage (75.57 ± 0.59) and water hyacinth silage (63.68 ± 3.75), respectively (p<0.05). The average pH level of hyacinth silage was lowest value (3.93 ± 0.79), followed by husk and corn cobs silage (4.71 ± 0.35) and Para grass silage (4.73 ± 0.18), respectively (p<0.05). These result showed the signified of relationship between the decrease of organic matter when the pH of silages were decreased.